Identifying biomarkers of hepatic fatty acid metabolism disorder in sevoflurane-induced brain developmental injury by bioinformatics analysis - Yuan, Haozheng; Lv, Yuying; Fan, Pei; Jia, Pengyu; Wang, Kui; Hu, Kailing; Sun, Haodong; Chen, Xinlin; Zhang, Pengbo (Frontiers in Molecular Neuroscience, 2025)
IntroductionExposure to sevoflurane in neonatal rats disrupts energy metabolism during brain development, which is associated with anesthetic-induced neurodevelopmental toxicity. Hepatic fatty acid metabolism plays a critical role in response to brain energy supply. However, how sevoflurane exposure affect hepatic fatty acid metabolism remains unclear.MethodsWe employed multiple analytical methods in neonatal rats following sevoflurane exposure to: (1) Analyze alterations in hepatic fatty acid metabolism-related gene expression and immune cell infiltration; (2) Decipher associated metabolic pathways, including cholesterol metabolism and the expression changes of Dhcr24; (3) Conduct enrichment analyses (GO, KEGG, GSEA, GSVA) and functional investigations via Friends analysis; (4) Construct mRNA-miRNA-lncRNA regulatory networks; (5) Identify key genedrug small molecule interactions based on IC50 differences and (6) Verify the expression of key genes involved in fatty acid metabolism and the activation of immune cells.ResultsSignificant alterations were observed: (1) Identification of 15 key fatty acid metabolism-related differentially expressed genes (DEGs and RT-PCR); (2) Significant enrichment of 40 GO terms and 5 KEGG pathways; (3) GSEA/GSVA revealed 130 up-regulated and 62 down-regulated GO gene sets, along with 5 up-regulated and 2 down-regulated KEGG pathways; (4) Friends analysis highlighted Dhcr24 as a critical player in cholesterol metabolism; (5) Network analysis identified pivotal mRNA and lncRNA nodes within the regulatory networks; (6) Screening yielded 43 key gene-drug combinations with significant IC50 differences; and (7) Immunofluorescence confirmed the activation expression of relevant immune cells. Bioinformatics analysis pinpointed diagnostic biomarkers for both hepatic fatty acid metabolism perturbations and immune cell infiltration following exposure.DiscussionThese findings demonstrate that neonatal sevoflurane exposure profoundly affects hepatic fatty acid metabolism and immune cell infiltration, involving specific key genes (including Dhcr24), perturbed pathways, and regulatory networks. The identified biomarkers and potential therapeutic targets provide a crucial foundation for developing more specific countermeasures against sevoflurane-induced neurodevelopmental toxicity, potentially via targeting the liver-brain metabolic axis.